Development of low carbon concrete with high cement replacement ratio by multi-response optimization - Suliman Khan; Safat Al-Deen; Chi King Lee (Cleaner Materials)
This study develops three new Low Carbon Concrete (LCC) mix designs with characteristic cylinder compressive strengths of 32 MPa (C32), 25 MPa (C25), and 20 MPa (C20). By using a Taguchi design of experiment (T-DoE) model and combined it with Grey relational analysis (GRA) and Principal component analysis (PCA) for multi-response optimization, sixteen trial mixes employing supplementary cementitious materials (SCMs) to replace 80 % to 95 % of ordinary Portland cement (OPC) were tested. Three factors namely, OPC replacement percentage, ground granulated blast-furnace slag (GGBFS) to fly ash (FA) ratio, and silica fume (SF) to binder percentage were considered. Optimization results led to three LCC mix designs with 80 %, 85 %, and 90 % OPC replacement. Their compressive strength, split tensile strength, flexural strength, elastic modulus, and slump were evaluated. Confirmation tests showed that the 80 %, 85 % and 90 % OPC replacement mixes respectively satisfied requirements for C32, C25, and C20 concretes. Carbon footprint study showed that the LCC mixes led to significant reduction of carbon footprint when compared with OPC concrete. Finally, microstructure analysis was conducted to study in the microstructure characteristics of the LCCs.